Numerical simulation of an elementary Vortex-Induced-Vibration problem by using fully-coupled fluid solid system computation - Pomarède, M; Longatte, E; Sigrist, J (The International Journal of Multiphysics, 2010)
Numerical simulation of Vortex-Induced-Vibrations (VIV) of a rigid circular elastically-mounted cylinder submitted to a fluid cross-flow has been extensively studied over the past decades, both experimentally and numerically, because of its theoretical and practical interest for understanding Flow-Induced-Vibrations (FIV) problems. In this context, the present article aims to expose a numerical study based on fully-coupled fluid-solid computations compared to previously published work [34], [36]. The computational procedure relies on a partitioned method ensuring the coupling between fluid and structure solvers. The fluid solver involves a moving mesh formulation for simulation of the fluid structure interface motion. Energy exchanges between fluid and solid models are ensured through convenient numerical schemes. The present study is devoted to a low Reynolds number configuration. Cylinder motion magnitude, hydrodynamic forces, oscillation frequency and fluid vortex shedding modes are investigated and the “lock-in” phenomenon is reproduced numerically. These numerical results are proposed for code validation purposes before investigating larger industrial applications such as configurations involving tube arrays under cross-flows [4].